Rational design of live attenuated vaccine by site-directed mutagenesis and deletion in the 5’- non coding region of the enterovirus 71(EV-A71) genome - Yee, Isabel Pin Tsin * (2015)
The Hand, Foot and Mouth Disease is caused by a group of Enteroviruses such as Enterovirus 71 (EV-A71) and Coxsackievirus CV-A6, CV-A10, and CV-A16. Mild symptoms of EV-A71 infection in children range from high fever, vomiting, rashes and ulcers in mouth, commonly affecting children and infants. EV-A71 can produce more severe symptoms such as brainstem and cerebellar encephalitis, leading up to cardiopulmonary failure and death. The lack of vaccines and antiviral drugs against EV A71 highlights the urgency of developing preventive and treatment agents against EV A71 to prevent further fatalities. The molecular basis of virulence in EV-A71 is still uncertain. It remains to be investigated if there is a universal molecular determinant present in every EV-A71 fatal strain or whether every fatal strain differs in virulence determinant depending on their sub-genotype. In this study, genetically modified EV A71 virus was constructed by substituting nucleotides at positions 158, 475, 486, and 487 based on the neurovirulence of poliovirus Sabin strains 1, 2 and 3. The single nucleotide difference between the fatal strain 41 (5865/Sin/000009) and the non-fatal strain (strain 10) was investigated to see if it is responsible for neurovirulence by introducing a nucleotide substitution (Guanine) at position 5262 in the EV-A71 strain 41 genome. Another mutant strain was also constructed through partial deletion of the 5’ NTR region in the EV-A71 genome. The virulence of the mutated EV-A71 strains were evaluated in Rhabdomyosarcoma cell culture by plaque assays, tissue culture infectious dose (TCID50) determinations, real time Reverse-Transcriptase Polymerase Chain Reaction (RT-PCR) and production of VP1. It was observed that mutants 475 and the partial deletant (deletion from nt. 475-485 in the 5’NTR) had minimal cytopathic effects as compared to mutants 158, 486, and 5262 when transfected with RD cells. This was 4 consistent with the RT-PCR results that showed the viral RNA copy number for mutants 475, 487 and partial deletant (5’NTR) to be of lowest amount when RNA was extracted from transfected RD cells. The partial deletant (PD) may be the most stable mutant genetically as it demonstrated high immunogenicity (neutralizing titre of 1:32) and low pathogenicity and hence, could be a good potential LAV candidate for further studies. In addition, intraperitoneal administration of the heat-inactivated EV-A71 mutants 158, 475, 486, 487, 5262 and PD and the homologous EV-A71 whole virion in the murine model triggered both cellular and humoral immune response. The data collectively indicated that every fatal EV-A71 strain differs in virulence determinant depending on their sub-genotype. Differences in nucleotide substitutions in the various mutants were reflected in the differences observed in immunogenicity based on the neutralizing titres of mice antisera. Hence, vaccines can be rationally designed to treat different EV-A71 genotypes and sub-genotypes.